Association of HLA-B Gene Polymorphisms with Type 2 Diabetes in Pashtun Ethnic Population of Khyber Pakhtunkhwa, Pakistan. (16th June 2021) - Jan, Asif; Saeed, Muhammad; Afridi, Muhammad Hussain; Khuda, Fazli; Shabbir, Muhammad; Khan, Hamayun; Ali, Sajid; Hassan, Muhammad; Samiullah,; Akbar, Rani; Zakiullah,
Abstract : Human leukocyte antigen (HLA) system is the most polymorphic and gene dense region of human DNA that has shown many disease associations. It has been further divided into HLA classes I, II, and III. Polymorphism in HLA class II genes has been reported to play an important role in the pathogenesis of type 1 diabetes (T1D). It also showed association with T2D in different ethnic populations. However, a little is known about the relationship of HLA class I gene polymorphism and T2D. This study has evaluated the association of HLA-B (class I gene) variants with T2D in Pashtun ethnic population of Khyber Pakhtunkhwa. In the first phase of the study, whole exome sequencing (WES) of 2 pooled DNA samples was carried out, and DNA pools used were constructed from 100 diabetic cases and 100 control subjects. WES results identified a total of n = 17 SNPs in HLA-B gene. In the next phase, first 5 out of n = 17 reported SNPs were genotyped using MassARRAY® system in order to validate WES results and to confirm association of selected SNPs with T2D. Minor allele frequencies (MAFs) and selected SNPs×T2D association were determined using chi-square test and logistic regression analysis. The frequency of minor C allele was significantly higher in the T2D group as compared to control group (45.0% vs. 13.0%) (p = 0.006 ) for rs2308655 in HLA-B gene. No significant difference in MAF distribution between cases and controls was observed for rs1051488, rs1131500, rs1050341, and rs1131285 (p > 0.05 ). Binary logistic regression analyses showed significant results for SNP rs2308655 (OR = 2.233, CI   95 % = 1.223 ‐ 4.077, and p = 0.009 ), while no considerable association was observed for the other 4 SNPs. However, when adjusted for these variants, the association of rs2308655 further strengthened significantly (adjusted   OR = 7.485, CI   95 % = 2.353 ‐ 23.812, and p = 0.001 ), except for rs1131500, which has no additive effect. In conclusion, the finding of this study suggests rs2308655 variant in HLA-B gene as risk variant for T2D susceptibility in Pashtun population.